Ownership structure, size, and banking system fragility in India: An application of survival analysis - Navneet Kaur; Santosh Kumar Shrivastava; Sarbjit Singh Oberoi (Economics: The Open-Access, Open-Assessment Journal, 2022)
The Reserve Bank of India has put 11 public sector banks under prompt corrective action and is planning to put three more where public sector banks constitute 68.9% of the total asset of the Indian banking industry based on 2018 figures; this raises a genuine concern for the financial health of the Indian banking sector as a whole. Under these considerations, this study is conducted to estimate the survival of banks based on ownership and size and uses the Cox proportional hazards model. This study has not found any significant difference in the failure risk of both public and private sector banks based on ownership. However, the study found a significant difference in the failure risk of banks based on size. The smaller banks are indeed at a higher risk of failure than larger banks. The findings of this study can be used to create an early warning system for smaller banks in India.
Keywords: 330; financial indicators; hazards function; ownership; size; survival analysis